2015
DOI: 10.1016/j.jjcc.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Exercise stress testing enhances blood coagulation and impairs fibrinolysis in asymptomatic aortic valve stenosis

Abstract: Asymptomatic moderate-to-severe AS patients respond to exercise with more pronounced and prolonged increase in thrombin generation, together with impaired fibrinolysis as compared to controls. Repeated episodes of exercise-induced prothrombotic state in AS might contribute to the progression of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Asymptomatic patients with moderateto-severe aortic valve stenosis demonstrated prothrombotic alterations in coagulation and fibrinolysis markers during exercise stress testing, reacting to exercise with more prominent and extended thrombin production and impaired fibrinolysis. The authors of this study concluded that exercise-induced prothrombotic states may contribute to progression of the disease [90].…”
Section: Coagulation and Fibrinolysismentioning
confidence: 84%
“…Asymptomatic patients with moderateto-severe aortic valve stenosis demonstrated prothrombotic alterations in coagulation and fibrinolysis markers during exercise stress testing, reacting to exercise with more prominent and extended thrombin production and impaired fibrinolysis. The authors of this study concluded that exercise-induced prothrombotic states may contribute to progression of the disease [90].…”
Section: Coagulation and Fibrinolysismentioning
confidence: 84%
“…The same cohort was also investigated how stress echocardiography alters blood coagulation and fibrinolysis, as described in detail previously [22]. At rest AS patients had higher HGF and TGF-β but not IL-6, IL-10 and VEGF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sex- and age-matched individuals recruited from the hospital staff and relatives served as controls. The two groups have been described in detail previously [22]. Briefly, the exclusion criteria were: history of angina, myocardial infarction, stroke, dizziness, or syncope, another cardiac valve disease of more than a moderate degree, left ventricular (LV) ejection fraction (EF) <50%, prior or current atrial fibrillation, hyper- or hypothyroidism, diabetes treated with insulin, renal or liver dysfunction, chronic pulmonary disease, treatment with oral anticoagulants, thienopyridine or nonsteroidal anti-inflammatory drugs other than aspirin, known cancer, autoimmune disorders, inability to perform exercise testing.…”
Section: Methodsmentioning
confidence: 99%